Rancang Bangun Augmented Reality Book Edukasi “Apa yang Tidak Bisa Kulihat” - Ranti Rahmadhani; Chintiya Larashati (MASALIQ, 2026)
Although the use of augmented reality in early childhood education continues to develop, media that specifically visualize invisible phenomena through the integration of physical books, three-dimensional objects, animation, audio, and interaction remain limited. This study aimed to design and develop the educational Augmented Reality Book Apa yang Tidak Bisa Kulihat for children aged 3–6 years. The study employed a research and development approach with the stages of research, design, and development. A total of 25 respondents were selected using a purposive sampling technique. Data were collected through observation, Likert-scale questionnaires, open-ended questions, short interviews, and a literature review, and were then analyzed using descriptive quantitative and qualitative methods. The results of the study produced an interactive illustrated book with five features, namely AR Cover, AR Wind, AR Smell, AR Bacteria, and AR Sound. Alpha testing showed that six components, including navigation, functioned according to the design with a 100% success rate. The product was able to display three-dimensional objects, animation, audio, and interactive responses after the image target was recognized. These findings enrich the development of augmented reality-based early science learning media and demonstrate the potential of integrating physical books and digital technology as an interactive educational medium. Further testing involving children, parents, and teachers is needed to assess the learning effectiveness and ease of use of the product.